Meninjau Kembali Riba: Dampaknya terhadap Inovasi Perbankan Islam di Indonesia - Adi Susandi; Nadya Zahra Virliana (Muttaqien Publishing, Lembaga Penelitian dan Pengabdian kepada Mayarakat (P3M) STAI DR. KH.EZ. Muttaqien Purwakarta, 2025)
In Islamic finance’s development, riba (usury) remains a significant challenge affecting banking product innovation. This study examines how various interpretations of riba impact product development in Islamic financial institutions in Indonesia. The method used is a qualitative systematic literature review, with data drawn from scholarly works, fatwas issued by the National Sharia Council (DSN-MUI), and the operational practices of Islamic banks. Thematic analysis was used to identify key patterns and issues shaping Islamic financial products. The results show that from classical schools of thought to contemporary Islamic scholars, diverse understandings of riba have driven the formalization of contracts such as murabahah, ijarah, and musharakah. Although legally valid, these contracts often mimic conventional financial mechanisms and do not fully fulfill the ethical objectives of maqāṣid al-shar’iah, raising concerns about the authenticity and long-term credibility of Islamic banking. This study recommends a multidisciplinary approach focused on maqāṣid, encompassing Islamic legal theory, behavioral economics, and sociocultural analysis, to enhance product relevance and integrity. This approach is crucial to maintaining public trust and ensuring the development of Islamic finance as a value-based system responsive to the dynamics of the modern economy.